Craft entrepreneurialism and sustainable scale: resistance to and disavowal of the creative industries as champions of capitalist growth. Issue 5 (20th October 2018) - Luckman, Susan
ABSTRACT: Craft and design-led creative practices are presently enjoying a zeitgeist moment of popularity, driven by consumer demand for unique, innovative and/or handmade objects. However despite the capacity to scale-up, craftspeople and designer makers continue to challenge conventional capitalist ideas of what entrepreneurial "success" looks like. Drawing upon data from a 4-year study of Australian designer makers, this article problematizes the digital content-friendly growth and enterprise discourses at the heart of governmental desires for the creative economy; discourses that seemingly presume every entrant into the creative field aspires to be the multi-millionaire director of their own creative success story. It examines how the complex intersectionality of old understandings of artistic value and "doing what you love", today mingle with ethical consumption values, environmental attentiveness, non-urban creative practice, the gendered exclusions of the creative workforce, and human desires for "good work" (Hesmondhalgh & Baker, 2011), to present a more complex, socially embedded picture of the contemporary creative economy. One where the more-than-capitalism values of the arts and cultural industries persist.